Kontrol Suhu dan Pakan Burayak Ikan Cupang Menggunakan PLC Zelio Sr3b261bd dan NodeMCU ESP8266 - Kusumastuti, Sri; Suryono, Suryono; Wisaksono, Adi; Supriyati, Supriyati; Setya Kartika, Vinda (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
In the transition from the dry season to the rainy season, betta fish breeders are particularly affected. Betta fish cubs are prone to death. Betta fish fry are betta fish children after 1 to 7 days. The feedstock of betta fish cubs, namely water fleas, is greatly reduced due to overflowing water. Unstable temperature attacks the body resistance of betta fish cubs. This study designed and made a conditioning device for the growth of betta fish fry using PLC Zelio SR3B261BD and NodeMCU ESP8266.  Features of the tool consist of making artemia feed, distributing artemia feed, telling breeders to mix feed, controlling, and monitoring the temperature of the pond water. The results of the study showed that the device can work to hatch artemia eggs, distribute artemia to fry, notify farmers via telegram to mix feed, monitor the temperature, and maintain the temperature of the pond water in the range of 24?C - 27?C. The difference with previous fish farming research, this research adds a feature of making betta fish feed through the process of hatching artemia eggs.